(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
The achievements of pediatric anesthesiology and intensive care in recent years are reviewed. The author focuses on the humanization of critical care medicine in children, the effect of anesthesia on the developing brain, providing pain therapy in children, and also highlights problems in the field of respiratory support, diagnosis and intensive care of sepsis in children and newborns, nutritional support in children in critical conditions.